Oxytocin increases recognition of masked emotional faces - Schulze, Lars; Lischke, Alexander; Greif, Jonas; Herpertz, Sabine; Heinrichs, Markus; Domes, Gregor (Psychoneuroendocrinology, 2011)
The neuropeptide oxytocin has been shown to improve many aspects of social cognitive functioning, including facial emotion recognition, and to promote social approach behaviour. In the present study, we investigated the modulatory effects of oxytocin on the recognition of briefly presented facial expressions. In order to diversify the degree of visual awareness for the facial stimuli, presentation duration was systematically varied. Fifty-six participants were administered intranasal oxytocin or a placebo in a double-blind, randomized, between-subjects design. Participants viewed angry and happy target faces or neutral distractors for 18, 35, or 53ms subsequently masked by neutral faces. Participants had to indicate the presence or absence of the briefly presented target face. Discrimination indices (d′) showed that oxytocin generally enhanced detection accuracy of emotional stimuli. This effect was more pronounced for the recognition of happy faces. We provide evidence that a single dose of intranasally administered oxytocin enhances detection of briefly presented emotional stimuli. The possible role of stimulus valence and recognition difficulty is discussed.
Gesehen am 28.10.2022